Comparison of mesophilic and thermophilic biohydrogen production amended by nickel-doped magnetic carbon. (10th October 2020) - Zhao, Wenqian; Zhang, Jishi; Zhang, Huiwen; Yang, Mengchen; Zang, Lihua
Abstract: The use of carbon composites and trace elements in biogas production has been demonstrated as an efficient approach. However, the relationship between carbon materials and the microbial community needs further clarification. In this study, a novel nickel-doped magnetic carbon material was produced to compare its role in biohydrogen (bioH2 ) production under mesophilic (37 °C) and thermophilic (55 °C) conditions. Material characterization showed that NiFe2 O4 and Ni(OH)2 were well doped into the activated carbon without obviously reducing its specific surface area. A moderate amount (200–600 mg/L) of magnetic carbon boosted bioH2 production, while excess magnetic carbon inhibited bioH2 evolution. The highest H2 yields of 260 and 192 mL/g glucose were found at 600 mg/L (37 °C) and 800 mg/L magnetic carbon (55 °C), which were 46.9% and 60.0% higher than the control yields, respectively. The microbial community revealed that such magnetic carbon significantly increased the abundance of Clostridium sensu stricto 1 (57.91%) in the mesophilic process, and Clostridium sensu stricto 7 (24.29%), 8 (7.39%) and 10 (24.85%) were the dominant bacteria in thermophilic fermentation. The results also showed that the production of clean energy with a higher yield of H2 and a low cost of production was achieved at 37 °C compared with those at 55 °C. Graphical abstract: Image 1 Highlights: Nickel-doped magnetic carbon (NDMC) was produced to improve bioH2 evolution. NDMC exhibited better properties than activated carbon in H2 fermentation. NDMC played different roles in mesophilic and thermophilic H2 production. NDMC selected Clostridium sensu stricto 1 as the dominant bacteria at 37 °C. The highest H2 yield of 260 mL/g glucose was obtained at 37 °C.